PENILAIAN KESEHATAN KEUANGAN PERUSAHAAN ASURANSI MENGGUNAKAN RISK BASED CAPITAL (RBC) - Nurul Nabila Batin; Sri Hartati Setyowarni; Herman (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2022)
The purpose of this study is to assess the financial health of insurance companies for the 2018-2020 period listed on the Indonesia Stock Exchange (IDX) using the Risk Based Capital method. This type of research uses a descriptive analysis method with a quantitative approach, with indicators of allowable assets, liabilities (liabilities), and minimum solvency level limits. The research sample used purposive sampling technique. From the results of the purposive sampling technique, 7 insurance companies are listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The results obtained from the assessment of the financial health of insurance companies using Risk Based Capital in 2018-2020 there are 3 companies that have very good Risk Based Capital values in the 2018-2020 period, namely ABDA, AMAG, and ASBI.